2009
DOI: 10.1089/pho.2007.2170
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Bond Strength of Single-Step Self-Etch Adhesives to Er:YAG Laser-Irradiated Dentin

Abstract: Objective: The purpose of this study was to evaluate the influence of Er:YAG laser irradiation on the bond strength to dentine of three single-step adhesives (AQ Bond Plus, G-Bond, and Clearfil Tri-S Bond), and one two-step self-etch adhesive (Clearfil Megabond) as a control. Background Data: The vast majority of the numerous reports on resin bonding to Er:YAG-lased dentine have concluded that Er:YAG laser irradiation is less effective in terms of bond strength, because of the sub-surface damage it produces. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
1
6
0
3
Order By: Relevance
“…However, we cannot say for certain whether the fracture occurred in the topmost layer of the laser-treated dentin, but the mainly adhesive fracture behavior can possibly be seen to be in line with the higher values of the shear bond tests. Several studies have shown that laser irradiation causes subsurface damage, and this could explain cohesive fractures occurring within the dentin [22,25]. This weakened dentin may be a reason for the lower shear bond values in other studies.…”
Section: Discussionmentioning
confidence: 82%
“…However, we cannot say for certain whether the fracture occurred in the topmost layer of the laser-treated dentin, but the mainly adhesive fracture behavior can possibly be seen to be in line with the higher values of the shear bond tests. Several studies have shown that laser irradiation causes subsurface damage, and this could explain cohesive fractures occurring within the dentin [22,25]. This weakened dentin may be a reason for the lower shear bond values in other studies.…”
Section: Discussionmentioning
confidence: 82%
“…On the other hand, as an all-in-one adhesive, SBP needs to possess a self-etching function, and therefore contains water and ethanol. Due to this difference in composition, all-in-one adhesives have lower viscosity than 2-step-etch adhesives 14,16) . Consequently, they blend on the TZP surface better than 2-step-etch adhesives 2) , which may increase bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…Cavities prepared with Er:YAG laser show irregular margins and rugged cavity walls and a rough floor, that differs from the essential principles of cavity preparation found by Black 6) . The surface asymmetry of laser-irradiated dentin appears well suited to adhesive restorations, although some reports have cast doubts on the bonding capacity of irradiated dentin 7,8) . Since the approval by the U.S. Federal Drug Administration in 1997 of the use of the Er:YAG laser for caries removal, in addition to cavity preparation and conditioning of tooth texture, there have been many reports on its use, in combination with composite materials [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%